Awareness and Application of Internet of Things in Universities Libraries in Kwara State, Nigeria - Saliu, Abdulfatai (International Journal of Knowledge Content Development & Technology, 2024)
The study was conducted on the awareness and application of internet of things in universities libraries in Kwara State, Nigeria. the study formulated used four research questions and used eighty five (85) samples as the population using total enumerative sampling techniques. A survey method was used in undertaking the study, in which answers were sought on the level of awareness of the internet of things in universities libraries in Kwara State, the extent of application of the internet of things in universities libraries in Kwara State, the benefit of internet of things in universities libraries in Kwara State, the challenges faced in the application of internet of things in universities libraries in Kwara State. The data collected from the study were analyzed using frequency tables and percentage. The study discovered that there the students are aware of the internet of things in universities libraries in Kwara State and the benefit of internet of a things include: Device in the IoT platforms are heterogeneous and are based on different hardware platforms and networks, It gives the high level of interoperability and interconnectivity, IoT platform has sensors which detect or measure any changes in the environment to generate data that can report on their status or even interact with the environment, IoT comes with the combination of algorithms and computation, software & hardware that makes it smart and Anything can be interconnected with the global information and communication infrastructure and the study identified data interpretation problem, Lack of skilled and specialized workers, Cost and Challenges in online security as well as Software complexity are major challenges faced in the application of internet of things in universities libraries in Kwara State. In conclusion the study made some recommendations which include that: Future libraries should be equipped with new technologies and networking devices as soon as possible. As this will be essential for users and librarians to have sufficient knowledge about IOT technologies.